GAMBARAN SELF AWARENESS PADA SISWA KELAS XI SMA NEGERI 1 INDRALAYA - Anggraini, Suci; Mega Putri, Rani (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Self-awareness is an important skill that adolescents need to have to understand their emotions, thoughts, and behaviors in the process of forming their identity. This study was motivated by the phenomenon of students who still have difficulty in recognizing and evaluating themselves optimally. The purpose of this study was to determine the level of self-awareness in grade XI students at SMA Negeri 1 Indralaya. This study used a descriptive quantitative approach with a sample of 80 students selected by simple random sampling. Data collection was carried out using a self-awareness scale based on three aspects: emotional awareness, accurate self-assessment, and self-confidence. The results showed that the majority of students had a level of self-awareness in the moderate category of 35%, followed by the low category of 29%, high 19%, very high 10%, and very low 8%. The three aspects measured also showed that most students were in the moderate category. These findings indicate that students already have basic abilities in recognizing themselves, but still need further development to achieve an optimal level of self-awareness in supporting their personal and social development.